Effect of the Different Synthetic Parameters on the Morphology and Magnetic Properties of Nickel Nanoparticles - Venegas-Yazigi, D; Venegas-Yazigi, D; Casagrande-Denardin, J (2014)
Coated stable metallic nickel nanocrystals (fcc-Ni) forming micro- and nanoaggregates with different morphologies have been synthesized through a one-pot NiII reduction process in the presence of l-serine (Ni-1 to Ni-5). The subsequent warming under solvothermal conditions of the spherical nickel particles (Ni-1) with ethylene glycol (EG) modifies the morphology of the initial spheres to hexagonal-quasi circular plates, which are disposed as a 3D arrangement (Ni-4). Electron microscopy images indicate that the size of these aggregates is 2 ?m, the thickness of the plates being ca. 110-200 nm. The magnetic measurement results for Ni-4 show a ferromagnetic behaviour with both enhanced coercivity (92 Oe) and magnetic remanence (7 emu g-1), and lower magnetic saturation (43 emu g-1), as compared with bulk nickel. The enhancement of the ferromagnetic properties observed for all the studied NPs is attributed to their dependence on the shape anisotropy and dipolar interactions. © 2014 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.